Transformation of Prophetic Law in Pancasila Values Viewed from the Wadas Village Conflict - Setiawan, Adam (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2022)
The conflict that occurred in Wadas Village shows that the government uses a power approach and repressive measures. This is in line with the perspective of legal positivism. Therefore, legal positivism has been judged to be incompatible with legal developments in Indonesia, giving rise to new perspectives, one of which is prophetic law. The purpose of the reaserch was to determine the extent of the transformation of professional law contained in Pancasila and to find out in the development of law in Indonesia by looking at the cases that occurred in Wadas Village. This research used narrative qualitative type, in the form of stories, events, written and unwritten documents. The results of the study show that the essence of prophetic law is to make religious values an important part in building civilization. Prophetic law refers to the will of Allah SWT which was revealed through the Prophets and Rasul, the Mualim and Aulia who are always istiqomah and hold fast to the ilahiyah line or sunnatullah. The prophetic legal foundation in Pancasila, Pancasila is the objectification of Islam in Indonesia. This means that Islam is its objective form in the crystallization of Pancasila thought. In the context of the Wadas Village conflict, the government uses a professional paradigm that prioritizes the interests of the community and uses a persuasive approach that leads to common interests, in order to know the will of the residents with the aim of making joint decisions without the interests of the Wadas Village residents.